1998
DOI: 10.1097/00042560-199807010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression in a Cohort of Infants With Vertically Acquired HIV Infection Observed From Birth: The Women and Infants Transmission Study (WITS)

Abstract: Reaching specific clinical or immunologic stages were strong predictors of progression to AIDS or death. Early onset of clinical signs (onset of lymphadenopathy, hepatomegaly, or splenomegaly < or =3 months of age), and early culture positivity (within the first 48 hours or within the first week of life), defined the infant with highest risk of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 28 publications
0
16
0
2
Order By: Relevance
“…This population of children is known to progress more rapidly to AIDS, with strong evidence of efficacy of early treatment [4,8,34], which indicates the need for earlier interventions for the treatment of HIV infection. Based on this evidence, since 2009 Brazil has adopted measures on their therapeutic guidelines recommending the treatment of all HIV infected children < 1 year of age regardless of clinical symptoms, immunological classification or HIV viral load [35].…”
Section: Discussionmentioning
confidence: 99%
“…This population of children is known to progress more rapidly to AIDS, with strong evidence of efficacy of early treatment [4,8,34], which indicates the need for earlier interventions for the treatment of HIV infection. Based on this evidence, since 2009 Brazil has adopted measures on their therapeutic guidelines recommending the treatment of all HIV infected children < 1 year of age regardless of clinical symptoms, immunological classification or HIV viral load [35].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that children under the age of 12 months are 1.7 times more likely to be subject to late-stage diagnosis and had higher rates of disease progression and mortality com- pared with older children 5,27,28,29 , even in children with high CD4 cell counts 30 . Considering this high risk, all children in this age group should receive ART, regardless of clinical conditions, CD4 counts, or viral load 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Hepatomegaly, hepatosplenomegaly and splenomegaly were placed in stage 2 rather than stage 1 as their presence has been associated with more rapid progression. 19,20 Stages 3 and 4 include conditions seen with progressive disease, stage 4 being more serious and more likely to result in early death. Pulmonary tuberculosis is in stage 3.…”
Section: World Health Organization Classificationmentioning
confidence: 99%